Pengaruh Partisipasi Penyusunan Anggaran, Komitmen Organisasi dan Motivasi Terhadap Kinerja Manajeial Pada Bank NTT Cabang Ende - Tajudin, Baharia; Sayang, Sabulon; Marselina, Apriana (Program Studi Akuntansi Universitas Flores, 2021)
This study aims to determine the effect of each variable, namely budgeting, organizational commitment, and motivation on managerial performance at Bank NTT Ende Branch. The population in this study were branch managers, deputy leaders, heads of cash, head of units, deputy chief of cash, deputy head of units and section leaders at the Ende Branch NTT Bank involved in the process of budget participation totaling 30 people. The sample in this study used the census method because the entire population was sampled. For the independent variable (X) in this study are budgeting participation (X1), Organizational Commitment (X2), Work motivation (X3). For the dependent variable (Y) in this study is Managerial Performance. The method used is quantitative research methods. This study uses primary data, namely questionnaires and secondary data, namely articles and journals. In this study using descriptive statistics, data quality test, classic assumption test, multiple regression analysis, and hypothetical test and analyzed using SPSS 24 application. The results showed that the effect of budgeting participation had a significant effect on managerial performance, organizational commitment had a significant effect on managerial performance, motivation had a significant effect on managerial performance.